Biocompatibility of a Coacervate-Based Controlled Release System for Protein Delivery to the Injured Spinal Cord - Rauck, Britta M. (Acta Biomater, 2014)
The efficacy of protein-based therapies for treating injured nervous tissue is limited by the short half-life of free proteins in the body. Affinity-based biomaterial delivery systems provide sustained release of proteins, thereby extending the efficacy of such therapies. Here, we investigated the biocompatibility of a novel coacervate delivery system based on poly(ethylene argininylaspartate diglyceride) (PEAD) and heparin in the damaged spinal cord. We found that the presence of the [PEAD:heparin] coacervate did not affect the macrophage response, glial scarring, or nervous tissue loss, which are hallmarks of spinal cord injury. Moreover, the density of axons, including serotonergic axons, at the injury site and the recovery of motor and sensorimotor function were comparable in rats with and without the coacervate. These results revealed the biocompatibility of our delivery system and supported its potential to deliver therapeutic proteins to the injured nervous system.